Complete mitochondrial genome of Min pig in nucleus herd. Issue 3 (2nd July 2020) - Wang, Lijuan; Wang, Li; Liu, Jianming; Di, Shengwei
Abstract: In this study, the complete mitochondrial genome of Min pig ( Sus scrofa ) in nucleus herd was sequenced in order to develop the mitogenome data for genus Sus . The complete mitogenome sequence is 16, 719 bp in length, containing a D-loop region, 13 protein-coding genes, 2 ribosomal RNA, and 22 transfer RNA genes. The new sequenced complete mitogenome of Min pig in nucleus herd will provide useful information for application in conservation genetics and evolution for this Near Threatened pig genomes.